The wiggly world of organization : muddling through with purpose, courage and skill - Rodgers, Chris, 1950- (Abingon, Oxon ; New York, NY : Routledge, 2021)
"The well-ordered, fully aligned view of organization and management practice, with its unfailingly positive results, bears little relationship to the world that managers and others experience every day. This straight-line, 'do this and you'll get that' idealization is far removed from the wiggly reality. Despite this, the former continues to dominate the ways in which management is spoken about and judged in formal organizational arenas and wider society. This creates unrealistic expectations of what managers (from CEO to the front line) can sensibly achieve independently of the actions of others. Crucially, too, it distorts the ways in which they and others account formally for their actions. And so, the fantasy continues. Against this background, the book offers a radically different way of thinking about, and engaging with, the irreducible complexity of organization and management practice. Using straightforward language throughout, it sets out to help managers and others to become consciously aware of what they already know deep down about how organization works and what they - and everyone else - are actually doing in practice. It then offers a practical approach to everyday practice that takes complexity seriously. Armed with these new insights, readers will be better placed to apply their innate understanding and practical judgement to the demands that they and others face day to day. Whether these arise from their roles as managers, other practitioners, policy makers, regulatory authorities, or participants more generally"--
OCLC-licensed vendor bibliographic record.
Keywords: Organizational change; Management; BUSINESS & ECONOMICS / Strategic Planning; BUSINESS & ECONOMICS / Decision-Making & Problem Solving